High‐order CFD methods: current status and perspective. (24th January 2013) - Wang, Z.J.; Fidkowski, Krzysztof; Abgrall, Rémi; Bassi, Francesco; Caraeni, Doru; Cary, Andrew; Deconinck, Herman; Hartmann, Ralf; Hillewaert, Koen; Huynh, H.T.; Kroll, Norbert; May, Georg; et al.
SUMMARY After several years of planning, the 1st International Workshop on High‐Order CFD Methods was successfully held in Nashville, Tennessee, on January 7–8, 2012, just before the 50th Aerospace Sciences Meeting. The American Institute of Aeronautics and Astronautics, the Air Force Office of Scientific Research, and the German Aerospace Center provided much needed support, financial and moral. Over 70 participants from all over the world across the research spectrum of academia, government labs, and private industry attended the workshop. Many exciting results were presented. In this review article, the main motivation and major findings from the workshop are described. Pacing items requiring further effort are presented. Copyright © 2013 John Wiley & Sons, Ltd.